2023
DOI: 10.1002/ange.202300446
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2‐Induced Amorphization in 2D Materials: Mechanism and Applications

Abstract: Supercritical carbon dioxide (SC CO2)‐assisted chemical and material processing has shown great success in the fabrication of 2D amorphous materials, while the amorphization mechanism in SC CO2 is quite complicated to be understand. In this review, we introduce different kinds of 2D amorphous materials prepared with SC CO2 and discuss the possible amorphization mechanism and how they affect the structures and properties of 2D materials. Their applications are further presented and discussed. In addition, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 186 publications
0
1
0
Order By: Relevance
“…The SAED pattern shows two different diffraction rings, indicating that the selected area of Al@zeolite is amorphous structure. Due to the stronger adsorption capacity of amorphous materials (Ge et al, 2023), the amorphous structure formed by Al@zeolite is bene cial to the removal of uoride ions.…”
Section: Microscopic Morphology and Element Distributionmentioning
confidence: 99%
“…The SAED pattern shows two different diffraction rings, indicating that the selected area of Al@zeolite is amorphous structure. Due to the stronger adsorption capacity of amorphous materials (Ge et al, 2023), the amorphous structure formed by Al@zeolite is bene cial to the removal of uoride ions.…”
Section: Microscopic Morphology and Element Distributionmentioning
confidence: 99%
“…It is also suggested that the thinner 2D metastable material is more suited to being stabilized compared to thicker ones (γ f/s and γ el are all minimized in eq ). With these principles, the stabilization of metastable structure with a “surfactant” layer has been demonstrated in many cases. For example, in the supercritical fluid system, the surface energy of the fluid can be sensitively regulated in a broad region (an example of the plot of the surface energy close to the critical condition can be found in ref ), allowing the formation and stabilization of some metastable phases and amorphous surfaces. …”
Section: Challenges and Solutions In The Stabilization Fabrication An...mentioning
confidence: 99%
“…Direct fabrications of 2D HA metastable materials have rarely been reported. In contrast, in traditional materials, the creation of HA metastable surface was well established, which can be classified as the in situ growth (e.g., size confined, , high pressure/high temperature condition, epitaxial growth, solvent mediation, , and their combinations), intermediate solidification, and post-treatment (e.g., electrochemical process, high-temperature surface redox reaction, , cold H 2 plasma reduction, Joule heating, surface etching, and ion exchange ,,, ) (Figure ). We now focus on these techniques, aiming to guide potential strategies for the fabrication of 2D HA metastable materials.…”
Section: Challenges and Solutions In The Stabilization Fabrication An...mentioning
confidence: 99%
See 2 more Smart Citations